Immediate Effect of Kinesiotaping on Non-dominant Wrist Extensor Muscles:an Alteration in Handgrip Strength of Healthy Individuals - M. Rasyidin Alamsyah Siregar; Indrayuni Lukitra Wardhani; Nuniek Nugraheni Sulistiawaty; R A Meisy Andriana (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Background: Adequate function of wrist extensor muscles is essential for handgrip strength. Handgrip strength can be used as a health problem predictor in the future. Maintaining and increasing handgrip strength to reduce the risk of future mortality is noteworthy. Aim: To investigate the immediate effect of the kinesiotaping facilitation technique on the non-dominant wrist extensor muscles on handgrip strength of healthy individuals. Material and Methods: This study was conducted in August – September 2020. Twenty-two healthy men, aged 25 – 40 years and willing to participate in this study by signing the research agreement form was recruited from Medical Rehabilitation Departement RSUD Dr. Soetomo Surabaya, and randomized into kinesiotaping group and placebo taping group. The kinesiotaping group received kinesiotaping facilitation technique Y strip 50% stretched on the non-dominant wrist extensor muscles. The placebo taping group received non-elastic adhesive tape Y strip on the non-dominant wrist extensor muscles. Handgrip strength was measured using hydraulic handgrip dynamometer before and 30 minutes after kinesiotaping facilitation technique and placebo taping applied. Results: Alteration of handgrip strength is significant increase in kinesiotaping group compared to placebo taping group (p=0.036). Conclusion: Kinesiotaping facilitation technique on non-dominant wrist extensor muscles can immediately increase handgrip strength of healthy individuals.